Clinical Efficacy and Therapeutic Effectiveness of Oseltamivir in Pediatric Influenza Treatment: A Systematic Review (Asian Journal of Pharmaceutics (AJP), 2025)
Influenza viruses cause significant morbidity and mortality worldwide each year. Diagnosing influenza basedon clinical symptoms is challenging and requires laboratory confirmation for a precise diagnosis. Oseltamivir isfundamental in managing influenza; however, its effectiveness in children remains under scrutiny due to resistance.This systematic review assessed the clinical effectiveness of oseltamivir in treating children with influenza. Thereview included five studies that assessed the effectiveness of oseltamivir in treating influenza in children andadults across different settings. Studies have shown that oseltamivir decreases illness duration when administeredearly, and its combination with clarithromycin and naproxen reduces fever duration and hospital stay. Peramivirshowed slightly faster fever reduction than oseltamivir, though clinical outcomes remained similar. Shortercourses of oseltamivir prophylaxis may be equally effective, potentially reducing costs. Adding oseltamivir tostandard care is cost-effective, particularly in older adults with health conditions. This review confirms the limitedeffectiveness of oseltamivir in reducing flu symptoms in children when administered promptly, with potentialbenefits from combination therapy in severe pediatric cases.